Weed suppressiveness of paving joint filling materials under diverging water regimes. (1st July 2016) - De Cauwer, B; Faes, J; Biesemans, N; Claerhout, S; Reheul, D
Summary: Since 2015, chemical weed control on public pavements in Flanders has been banned. This necessitates alternative weed control strategies. In this study, growth chamber experiments evaluated the weed suppressive ability of different joint filling materials under various water regimes. The tested materials comprised five unbound standard fillers (white quartz sand, sea sand, limestone 0/2 mm, limestone 2/6.3 mm and porphyry 2/6.3 mm) and two innovative materials (Dansand ® and Eco Fugensand ® ). Their weed suppressiveness was tested in pure and organically polluted states. Germination and biomass accumulation of two weed species that are abundantly found on public pavements ( Lolium perenne and Taraxacum officinale ) were investigated. Germination and biomass accumulation were lowest in both innovative materials, irrespective of organic contamination level, plant species and water regime. Weed growth in the standard materials was affected by plant species and water regime. Monthly biomass accumulation increased with increasing monthly water supply and number of irrigation days. Furthermore, the materials best capable of reducing weed growth, under all water regimes, even when organically polluted, were the innovative materials and sea sand. The results of this study show that the implemented water regime can influence weed suppressiveness (absolute as well as relative) of a joint filler. Hence, to fully assess weed suppressive ability, commercially launched joint fillers should be tested under diverging water regimes.